If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -37 = 24 Reorder the terms: -37 + 2x = 24 Solving -37 + 2x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '37' to each side of the equation. -37 + 37 + 2x = 24 + 37 Combine like terms: -37 + 37 = 0 0 + 2x = 24 + 37 2x = 24 + 37 Combine like terms: 24 + 37 = 61 2x = 61 Divide each side by '2'. x = 30.5 Simplifying x = 30.5
| 3x^2-x=5 | | X=2x-7 | | 2x-3y=24 | | 6t-6=9t-36 | | k^2+4k-77=0 | | -9.3x+1.8=-52.8-1.5x | | 3.5+2x+5.5=10 | | 4x-10x-40+3=2(x-1) | | 7x+3x=6 | | (7)m-(9)m=(-12) | | x^2+5x+10=0 | | 3(w-2)-6w=-21 | | -2.06d+18=-10.48 | | 3a=144 | | 7m-9m=-12 | | x^2(x+9)+7(x+9)= | | -110=-4c-6c | | 3b+4=15 | | 5x+10=3x+24 | | 11x+(-6x)+11= | | 9r-8=6r+7 | | (x^4+y^2)(x^4-y^2)= | | 3(x+4)-(-4)=2x+8-4 | | 5x^6+5x^5-40x^4+35x^3= | | 2x-x=1.5 | | 4x-10=2x+12 | | x^2=(x-2)*(x+6) | | 3t+9t=60 | | m=n+8 | | 3x+5=5x-9 | | 7u+11.59=32.31 | | 3x+7=6x-11 |